The role of multiomics in revealing the mechanism of skin repair and regeneration - Shi, Shaoyan; Ou, Xuehai; Long, Jafeng; Lu, Xiqin; Xu, Siqi; Li, Gang (Frontiers in Pharmacology, 2025)
Skin repair and regeneration are crucial processes in restoring the integrity of the skin after injury, with significant implications for medical treatments and plastic surgery. Multiomics, an integrated approach combining genomics, transcriptomics, proteomics, and metabolomics, offers unprecedented insights into the complex molecular and cellular mechanisms involved in skin healing. This review explores the transformative role of multiomics in elucidating the mechanisms of skin repair and regeneration. While genomic studies identify the genetic basis of wound healing, transcriptomics and proteomics uncover the dynamic changes in gene and protein expression, and metabolomics provides a snapshot of metabolic alterations associated with wound healing. Integrative multiomics studies can also identify novel biomarkers and therapeutic targets for skin regeneration. Despite the technical and biological challenges, the future of multiomics in skin research holds great promise for advancing personalized medicine and improving wound healing strategies. Through interdisciplinary collaboration, multiomics has the potential to revolutionize our understanding of skin repair, paving the way for innovative treatments in plastic surgery and beyond.